Parental depression and child outcomes - is marital conflict the missing link? - Hanington, L.; Heron, J.; Stein, A.; Ramchandani, P. (Child: Care, Health & Development, 2012)
Background Both maternal and paternal depression during the perinatal period are associated with adverse effects on child outcomes. Attention has started to focus on the mechanisms mediating these relationships. Marital conflict may play a role in this context. Methods In a large cohort study, the Avon Longitudinal Study of Parents and Children ( n= 14 541 pregnancies), we aimed to (i) investigate the relative influences of parental postnatal depression and marital conflict on child outcomes and to attempt to determine the pathway(s) of risk; (ii) investigate the impact of two types of antenatal stress (parental depression and marital conflict) on child outcomes; and (iii) determine the relative contributions of antenatal and postnatal risk. Parents completed the Edinburgh Postnatal Depression Scale and a marital conflict scale during the second trimester and at 8 months postnatally. Child outcomes were assessed at 42 months using the Rutter revised pre-school scales. Results Marital conflict partially mediated the relationship between postnatal depression in both mothers and fathers and child outcomes, and acted as an independent risk for adverse outcomes. Parental depression (maternal and paternal) and marital conflict in the antenatal period were both associated with adverse effects which persisted even when postnatal stresses were taken into account. Conclusions These findings, if replicated, suggest that screening and intervention programmes targeted at parental depression and marital problems should be considered antenatally, as well as postnatally.